Human Milk in the Second Year Nutritional and Economic Considerations for Indonesia - Jon E. Rohde (Paediatrica Indonesiana, 1974)
That mother milk provides the ideal infant diet is accepted by all but the most myopic diehards of the processed milk industry. Mortality in breast fed infants may be as low as one tenth of that experienced amongst their unfortunate bottle fed peers who often succumb to the ravages of diarrhea, marasmus and opportunistic infections (Harfouche, 1970). Mother milk approaches an ideal composition for the human, is cheap, sterile, readily available and, provides protection against certain infections.